Implementation of Genetic Algorithm for Parameter Tuning of PID Controller in Three Phase Induction Motor Speed Control - Dedid Cahya Happyanto; Ardik Wijayanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2014)
Induction motor at low speeds has a tough speed setting sets the width of the range. This study tested by giving the load motor disorders to describe the condition. The method used for vector control system so that the resulting performance is good at setting the motor speed and torque. This method is used in setting the Proportional Integral Derivative (PID) Tuning parameter settings based on Genetic Algorithm (GA) to provide a dynamic response to changes in speed and load torque on the motor, so we get smoothness at any speed change and braking and maximum torque motors. Optimization function is required to obtain a new PID parameter values each input value changes or load disturbances, in terms of the initial determination of these parameters using Ziegler-Nichols method based on frequency response. Tests were performed at a speed of approximately 1800 rpm value rise time of about 10 seconds after generation added, at a rate of 1800 rpm rise time value of the average remains around 9 seconds, but slightly reduced the oscillations in the response, and the speed of approximately 1700 rpm rise time value of the average is 9 seconds. The test results show that GA-based PID controller has a good response in approximately 0.85% overshoot at the motor speed change and braking